الضمانات القانونية والقضائية في قانون الاستثمار الجديد - خيذري فايزة - جميل وردة احلام (المسيلة, 2023)
سا كان االستثسار يحتل مكانة ىامة عمى أساس أنو قؾام الحياة االقترادية، وأحج الخكائد التي مؽ شأنيا دفع عجمة التشسية السحمية، وفي عل الحاجة السمحة لمجولة الجدائخية مشيؾض باقترادىا الؾطشي الحي يعج في الغخوف الخاىشة أولؾية وطشية ، فقج كان لداما عمييا أن تفتح أسؾاقيا السحمية أمام االستثسارات ، وبسا أن اتجاه ىحه األخيخة نحؾ بمج معيؽ فخ التذجيعات والحؾافد السقجمة مؽ قبمو ، إضافة إلى مجى دون غيخه يتؾقف عمى مجى ت ؾ ؾفخ الحساية والزسان بذكل أخص وكحا إزالة كل ما مؽ شأنو إثارة مخاوف السدتثسخيؽ خوري عمى السذخع الج دا ا ئخي إق خا ا ر نغام وعخقمة السذخوع االستثساري، فإنو كان مؽ الز انؾني متكامل لحساية السدتثسخيؽ ومشو استقظاب وجحب أكبخ عجد مؽ رؤوس األمؾال انؾنية وقزائية ضسؽ قانؾن خيذ السذخع الج دا ا ئخي لعجة ضسانات االجشبية ، ىحا ما يبخر تك االستثسار الججيج رقؼ 18 - 22 . Abstract : Since investment is a great importance on the basis that it is the strength of economic life and one of the cornerstones to local development. Additionally, in the view of the urgent need of the Algerian state to promote its National economy, which under the current circumstances is a national priority, Algeria had to open its local markets to Investments. Also, since the latter's orientation towards a particular country depends solely on the availability of encouragement and incentives provided by the latter, in addition to the availability of protection and security mainly. As well as eliminating everything that rises investors' fears and block the investment project. It was necessary for the Algerian legislature to establish an integrated legal system to protect investors, thus attracting the largest number of foreign capital. This justifies the Algerian legislature's enshrinemen
Keywords: الضمانات القانونية - الضمانات القضائية - قانون الاستثمار الجديد